A dynamic capabilities perspective on pro-market reforms and university technology transfer in a transition economy. (May 2021) - Li, Yang; Tang, Yujie
Abstract: Pro-market reforms are a form of institutional change from a socialist economy to a market economy. As the institutional environment in a transition economy changes, pro-market reforms exert a significant influence on university technology transfer (UTT). By leveraging dynamic capabilities in the context of universities, this study develops a theoretical framework for analyzing how the scope (degree) and speed (rate) of pro-market reforms in a transition economy are related to UTT. Additionally, this study analyzes whether or not the relationship between the scope/speed of pro-market reforms and UTT differs across universities depending on staff size and university-industry (UI) linkages. To test our hypotheses, we use 1061 universities in 31 Chinese sub-national regions (provinces) from 2005 to 2013. The results show that a greater scope of pro-market reforms has a positive impact on UTT, while a greater speed of pro-market reforms has a negative impact on UTT. We also find that the positive relationship between the scope of pro-market reforms and UTT is more pronounced for universities with fewer staff members or more UI linkages, and the negative relationship between the speed of pro-market reforms and UTT is less pronounced for universities with more staff members or more UI linkages. Overall, this study opens avenues for understanding the relationship between pro-market reforms and UTT in a transition economy. Highlights: A greater scope of pro-market reforms has a positive impact on UTT. A greater speed of pro-market reforms has a negative impact on UTT. University staff size moderates the impact of the scope/speed of reforms on UTT. UI linkages moderates the impact of the scope/speed of reforms on UTT.